2008
DOI: 10.1007/s00128-008-9580-9
|View full text |Cite
|
Sign up to set email alerts
|

Trace Metal Concentrations in Nile Tilapia (Oreochromis niloticus) in Three Catchments, Sri Lanka

Abstract: Samples of the muscle and liver of the Nile tilapia (Oreochromis niloticus) were obtained from a single reservoir in each of three Sri Lankan catchments (Kaudulla, Rajanganaya, and Udawalawe reservoirs in the Mahaweli, Kala Oya, and Walawe Ganga river basins, respectively) in 2002. The concentrations of 12 elements were consistently detected in the tilapia muscle and liver (Ca, Cd, Cu, Fe, Hg, K, Mg, Mn, Na, P, Sr and Zn). However, a three factorial principal components analysis suggested that there were no di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…Previous studies have concluded that there is no correlation between the age of the reservoir and metal concentration (Allinson et al, 2009). Although some reservoirs sampled in this study were reconstructed long ago, Kaudulla and Minneriya were first constructed in the year AD 273 and 276, respectively (reconstructed 1958, 1903).…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…Previous studies have concluded that there is no correlation between the age of the reservoir and metal concentration (Allinson et al, 2009). Although some reservoirs sampled in this study were reconstructed long ago, Kaudulla and Minneriya were first constructed in the year AD 273 and 276, respectively (reconstructed 1958, 1903).…”
Section: Resultsmentioning
confidence: 79%
“…Moreover, in 2008, the highest inland fish production was recorded in the Anuradhapura district (9380 metric ton) while the Polonnaruwa district claimed for the second highest fish production (7320 metric ton) in the same year (NARA, 2009). Reservoir fish are the main source of animal protein of the rural people living in the dry zone of the country (Allinson et al, 2009) where most of the people living in that area are farmers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The condition factor of fish was calculated following Fulton's condition factor by dividing fish body weight (g) over [body length] 3 (cm) and multiplied to 100. The daily intake by Malaysian people was computed by the multiplication of measured concentration by 160 g of average weight of fish consumed daily [17]. Statistical analysis was conducted using IBM SPSS Statistics 24.…”
Section: Discussionmentioning
confidence: 99%